Project and problem based learning on students' critical thinking skills at cell material - Isti Citra Wulandari; Nuri Dewi Muldayanti; Anandita Eka Setiadi (JPBIO (Jurnal Pendidikan Biologi), 2020)
Based on observations when apprenticed at SMAN 7 Pontianak it was known that students' critical thinking skills are still low. Therefore, a variety of learning models are needed to improve students' critical thinking skills. The purpose of this research was to determine the differences and effective learning model in improving students' critical thinking skills between students taught using the project-based learning model and the problem based learning model. The research method used was a quasi-experiment with a nonequivalent control group design. The data collection techniques used were measurement. The results showed a significant value of the T-test was 0.000<0.05. This means that there are differences in students' critical thinking skills taught using the project-based learning model and problem-based learning. The average value of N-Gain in the project-based learning model was 0.69 (moderate) while the problem-based learning model was 0.58 (moderate), so the project-based learning model is more effective than the problem based learning model on students' critical thinking skills.Keywords: Critical thinking skills, problem-based learning, project-based learning, cell material